Enoxaparin utilization evaluation in inpatients with or at risk of thromboembolic disorders: A one-year, single-centered, retrospective Study - Shahram Ala; Gohar Eslami; Atieh sayftabar (Mazandaran University of Medical Sciences, 2016)
The aim of this study was evaluation of enoxaparin utilization in hospitalized patients who had received enoxaparin either for prophylaxis or for treatment of thromboembolic disorders. A total of  356 patients were included in this retrospective study and were analyzed for enoxaparin utilization in terms of prescription patterns, treatment strategy, dosing regimen, indications/contraindications, adverse drug reactions, bleeding events, drug-drug interactions and monitoring parameters. The inpatient records and charts were used to extract the relevant data. 47.8% of the patients were prescribed inappropriate doses of enoxaparin, and 35.7% were treated with enoxaparin for inappropriate duration. Lack of appropriate monitoring of platelet count, complete blood count (CBC), activated partial thromboplastin time (aPTT), serum potassium level and serum creatinine during enoxaparin therapy was also noted in nearly one third of the patients. Furthermore, dose adjustment was not performed for 85% of the patients who had elevated serum creatinine. Co-administration of enoxaparin and anti-platelet drugs (aspirin and clopidogrel) or non-steroidal anti-inflammatory drugs were noted in 72% of the patients. No cases of major bleeding occurred but hematuria was observed in 16.3% of the patients. High doses of enoxaparin (120 mg/day), concurrent administration of antiplatelet drugs and increased age were found to be the main risk factors for bleeding. Overall, inappropriate utilization of enoxaparin in terms of prescription, dosing regimen, drug interaction and monitoring was observed in a large proportion of the patients which indicates the need for more careful consideration of the patients' conditions and the treatment guidelines before treatment with enoxaparin in the studied healthcare setting.